Optimizing ride-sharing operations in smart sustainable cities: Challenges and the need for agile algorithms - Martins, Leandro do C.; de la Torre, Rocio; Corlu, Canan G.; Juan, Angel A.; Masmoudi, Mohamed A. (Computers & industrial engineering, 2021)
•Challenges in car sharing (ridesharing and carpooling) are discussed.•85 papers are reviewed.•Focus is on optimization and simulation techniques in carsharing.•First paper to introduce agile optimization to carsharing literature.•Multi-dimensional comparison of analytical approaches is provided. Mobility solutions like ride-sharing and carpooling are becoming popular in many urban and metropolitan areas around the globe. These solutions, however, create many operational challenges that need to be solved in order to make them more efficient and sustainable in time, e.g.: determining the number and location of parking slots, finding the optimal routes in terms of time or emissions, or developing synchronized schedules among ride-sharing users. This paper provides an updated review on car-sharing optimization studies (including ride-sharing and carpooling), compares different analytical approaches in this research area, and discusses the emerging concept of ‘agile’ algorithms as one of the approaches that might contribute to deal with the requirements of large-scale and dynamic car-sharing optimization problems.